A multiphase coupled magnesium-based composite hydrogen storage material and its preparation method and application

By introducing nano nickel powder and magnesium-rare earth alloy powder into magnesium-based composite hydrogen storage materials, a multi-phase coupling structure is formed, which solves the problem of slow hydrogen absorption and release of magnesium-based hydrogen storage materials, and achieves more efficient hydrogen storage and release.

CN119372535BActive Publication Date: 2025-03-25GUANGDONG INST OF NEW MATERIALS

Patent Information

Application Number
CN202411942519.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-25
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The hydrogen absorption and release rate of magnesium-based composite hydrogen storage materials is slow, the reaction kinetic performance is poor, and high temperature and pressure conditions are required. The high hydrogen release temperature increases energy consumption and cost, and limits the application of rapid hydrogen charging and discharging.

Method used

A multi-phase coupled magnesium-based composite hydrogen storage material is used to prepare raw materials including nano nickel powder and magnesium-rare earth alloy powder. Through ultrasonic dispersion, ball milling and activation treatment, a material containing a single layer of γ'' phase, a single layer of γ'' phase and 14H-LPSO phase is formed.

Benefits of technology

The hydrogen absorption, hydrogen release and hydrogen storage performance of magnesium-based composite hydrogen storage materials are significantly improved, the initial hydrogen release temperature is reduced, and the reaction kinetic performance of the material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372535B_ABST
    Figure CN119372535B_ABST
Patent Text Reader

Abstract

The invention discloses a multiphase coupled magnesium-based composite hydrogen storage material and a preparation method and application thereof, belonging to the technical field of hydrogen storage materials. The raw materials for preparing the multiphase coupled magnesium-based composite hydrogen storage material include nano nickel powder with a particle size of 100nm~500nm and magnesium-rare earth alloy powder with a particle size of 20μm~50μm; the nano nickel powder accounts for 5wt%~10wt% of the magnesium-rare earth alloy powder; the magnesium-rare earth alloy powder contains 1wt%~6wt% of rare earth. The grains of the multiphase coupled magnesium-based composite hydrogen storage material are distributed with 10vt%~15vt% of long-period ordered stacking 14H-LPSO phase, 2vt%~5vt% of single-layer γ'' phase and 5vt%~10vt% of single-layer γ' phase. The multiphase coupled magnesium-based composite hydrogen storage material has a smaller grain size, a higher hydrogen absorption and desorption amount, and a lower initial desorption temperature, and can be used in new energy vehicles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogen storage materials, and in particular to a multiphase coupled magnesium-based composite hydrogen storage material and a preparation method and application thereof. Background Art

[0002] Magnesium-based hydrogen storage materials are considered to be one of the most promising metal hydrogen storage materials due to their large hydrogen storage capacity, abundant resources and low cost. Moreover, the theoretical hydrogen storage capacity of magnesium-based composite hydrogen storage materials can reach 7.6%, and the hydrogen storage density is 1,000 times that of gaseous hydrogen and 1.5 times that of liquid hydrogen. As a reversible "storage" medium for hydrogen, magnesium-based hydrogen storage materials have excellent hydrogen absorption and desorption properties and the advantages of no kinetic decay and capacity loss in long-term cycles. They can achieve large-capacity solid-state hydrogen storage and long-distance transportation at room temperature and pressure. They can not only reduce the storage and transportation costs and energy consumption of hydrogen, but also are safe and convenient. They are expected to become an important key material in the field of hydrogen storage and transportation, thereby promoting the development of the hydrogen energy industry.

[0003] However, the absorption and desorption rate of magnesium-based composite hydrogen storage materials is slow, which is mainly due to their poor reaction kinetics. In the process of hydrogen absorption and desorption, higher temperature and pressure conditions are required. Moreover, the desorption temperature of magnesium-based composite hydrogen storage materials is relatively high, and usually higher temperatures are required to effectively release hydrogen. This increases energy consumption and cost during use, limiting its use in application scenarios that require rapid hydrogen charging and desorption.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The object of the present invention is to provide a multiphase coupled magnesium-based composite hydrogen storage material and a preparation method and application thereof, so as to solve or improve the above technical problems.

[0006] The present invention can be implemented like this:

[0007] In a first aspect, the present invention provides a multi-phase coupled magnesium-based composite hydrogen storage material, wherein the raw materials for preparing the multi-phase coupled magnesium-based composite hydrogen storage material include nano nickel powder and magnesium-rare earth alloy powder;

[0008] The nano nickel powder accounts for 5wt% to 10wt% of the magnesium-rare earth alloy powder, and the particle size of the nano nickel powder is 100nm to 500nm;

[0009] The magnesium-rare earth alloy powder contains 1wt% to 6wt% of rare earth, and the rare earth includes at least one of lanthanum, cerium, praseodymium, yttrium and neodymium; the particle size of the magnesium-rare earth alloy powder is 20μm to 50μm;

[0010] The multiphase coupled magnesium-based composite hydrogen storage material has 10vt%~15vt% long-period ordered stacking 14H-LPSO phase, 2vt%~5vt% single-layer γ" phase and 5vt%~10vt% single-layer γ' phase distributed inside the grains.

[0011] In an optional embodiment, the multiphase coupled magnesium-based composite hydrogen storage material further has at least one of the following characteristics:

[0012] Feature 1: The grain size of the multiphase coupled magnesium-based composite hydrogen storage material is 0.3μm~1μm;

[0013] Feature 2: The hydrogen absorption capacity of the multiphase coupled magnesium-based composite hydrogen storage material is not less than 4.0wt%;

[0014] Feature 3: The initial dehydrogenation temperature of the multiphase coupled magnesium-based composite hydrogen storage material is not higher than 300°C;

[0015] Feature 4: The hydrogen release capacity of the multiphase coupled magnesium-based composite hydrogen storage material is not less than 3.0wt%.

[0016] In a second aspect, the present invention provides a method for preparing a multiphase coupled magnesium-based composite hydrogen storage material as described in the aforementioned embodiment, comprising the following steps: ultrasonically dispersing nano-nickel powder and drying it; subsequently mixing it with magnesium-rare earth alloy powder and vibrating and dispersing it; then performing multiple ball millings in an alternating manner of high-energy ball milling and low-energy ball milling under the protection of an inert gas, followed by activation treatment.

[0017] In an optional embodiment, the frequency of ultrasonic dispersion is 20KHz~25KHz, and the time of ultrasonic dispersion is 20min~40min.

[0018] In an optional embodiment, the frequency of the vibration dispersion is 30 Hz to 40 Hz, and the time of the vibration dispersion is 30 min to 1 h.

[0019] In an optional embodiment, the rotation speed of the high-energy ball mill is 180 rpm to 250 rpm, the time of a single high-energy ball mill is 30 min to 1 h, and the ball-to-material ratio is 20:1 to 30:1.

[0020] In an optional embodiment, the rotation speed of the low-energy ball mill is 100 rpm to 150 rpm, the time of a single low-energy ball mill is 30 min to 1 h, and the ball-to-material ratio is 20:1 to 30:1.

[0021] In an optional embodiment, the high-energy ball milling and the low-energy ball milling are alternately performed 5 to 10 times.

[0022] In an optional embodiment, the activation treatment is performed at a temperature of 300° C. to 400° C. and a hydrogen pressure of 0.5 MPa to 3 MPa for 2 h to 3 h.

[0023] In a third aspect, the present invention provides an application of a multi-phase coupled magnesium-based composite hydrogen storage material according to the aforementioned embodiment in a fuel cell hydrogen storage system.

[0024] The beneficial effects of the present invention include:

[0025] The multiphase coupled magnesium-based composite hydrogen storage material provided by the present invention is prepared from a raw material with a specific composition and particle size. The multiphase coupled magnesium-based composite hydrogen storage material has 10vt% to 15vt% of a long-period ordered stacking 14H-LPSO phase, 2vt% to 5vt% of a single-layer γ'' phase, and 5vt% to 10vt% of a single-layer γ' phase distributed inside the grains, wherein the γ'' phase and the γ' phase play an important role in improving the hydrogen storage performance. The γ'' phase has a single-layer structure and can absorb hydrogen at a lower temperature, while the γ' phase can release hydrogen at a lower temperature. The presence of these two phases enables the magnesium-based hydrogen storage material to effectively and quickly absorb and release hydrogen under different temperature conditions. By controlling the ratio and distribution of the γ'' phase and the γ' phase within the scope of the present invention, the hydrogen storage and desorption capacity and hydrogen desorption temperature of the magnesium-based hydrogen storage material can be effectively optimized. The LPSO phase can promote the diffusion and adsorption of hydrogen atoms by providing a shorter hydrogen diffusion path and a lower energy barrier, thereby facilitating the improvement of the hydrogen storage rate and capacity of the material. The present invention promotes the generation of single-layer γ'' phase, single-layer γ' phase and small-sized 14H-LPSO phase by controlling the content and particle size of nano-nickel powder, and avoids the precipitation of coarse 18R-LPSO phase. Through the coupling effect between the single-layer γ'' phase, the single-layer γ' phase and the 14H-LPSO phase, the grain size of the magnesium-based composite hydrogen storage material can be significantly refined, the hydrogen absorption and desorption of the magnesium-based composite hydrogen storage material can be greatly increased, the initial desorption temperature can be reduced, and the hydrogen storage and desorption performance can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0027] Figure 1 This is a morphology image of the multiphase coupled magnesium-based composite hydrogen storage material prepared in Example 1;

[0028] Figure 2 This is a morphology diagram of the precipitated phase in the magnesium-based composite hydrogen storage material prepared in Example 1;

[0029] Figure 3 The atomic structure diagram of the γ'' phase in the multiphase coupled magnesium-based composite hydrogen storage material prepared in Example 1;

[0030] Figure 4 The atomic structure diagram of the γ' phase in the multiphase coupled magnesium-based composite hydrogen storage material prepared in Example 1;

[0031] Figure 5 The atomic structure diagram of the 14H-LPSO phase in the multiphase coupled magnesium-based composite hydrogen storage material prepared in Example 1;

[0032] Figure 6 This is a hydrogen absorption curve diagram of the multiphase coupled magnesium-based composite hydrogen storage material prepared in Example 1;

[0033] Figure 7 This is a hydrogen release curve of the multiphase coupled magnesium-based composite hydrogen storage material prepared in Example 1. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0035] The multiphase coupled magnesium-based composite hydrogen storage material provided by the present invention and its preparation method and application are described in detail below.

[0036] The invention provides a multiphase coupled magnesium-based composite hydrogen storage material. The raw materials for preparing the multiphase coupled magnesium-based composite hydrogen storage material include nano nickel powder and magnesium-rare earth alloy powder.

[0037] Among them, the nano nickel powder diffuses into the magnesium matrix and forms γ'' phase, γ' phase and 14H-LPSO phase with magnesium and rare earth elements. Compared with using other metal powders (such as Zn, etc.) as raw materials, the remaining nickel powder can also act as a catalyst to accelerate the hydrogen storage and release rate, which has obvious advantages. In magnesium-rare earth alloy powder, in addition to promoting the formation of γ'' phase, γ' phase and 14H-LPSO phase, the remaining rare earth itself can also react with hydrogen as a medium for hydrogen storage and release, significantly improving the hydrogen storage capacity of the material. For example, the rare earth can include at least one of lanthanum, cerium, praseodymium, yttrium and neodymium.

[0038] In the present invention, the nano nickel powder accounts for 5wt% to 10wt% of the magnesium-rare earth alloy powder, such as 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt% or 10wt%, etc., and can also be other values ​​within the range of 5wt% to 10wt%.

[0039] If the amount of nano-nickel powder is too little, it is not conducive to the formation of γ'' phase, γ' phase and 14H-LPSO phase, the volume fractions of the three phases are low, and the catalytic effect of nickel itself is difficult to manifest; if the amount of nano-nickel powder is too much, the nanoparticles are easy to agglomerate, which is not conducive to the uniform dispersion of material components, and the cost of nano-nickel powder is high. Excessive Ni is easy to form Mg2Ni with Mg, which wastes raw materials.

[0040] In the present invention, the particle size of the nano nickel powder is 100nm~500nm, such as 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm or 500nm, etc., and can also be other values ​​within the range of 100nm~500nm.

[0041] If the particle size of the nano-nickel powder is less than 100nm, the specific surface area of ​​the nano-nickel powder will be larger and the surface adsorption force will be stronger, which is not conducive to the uniform dispersion of the nano-nickel powder on the surface of the spherical magnesium powder; if the particle size of the nano-nickel powder is greater than 500nm, the activity is not as good as that of nanoparticles with moderate particle size, which is not conducive to the diffusion of nickel elements and interfacial reactions, resulting in low volume fractions of the γ' phase, γ' phase and 14H-LPSO phase, which is not conducive to improving the hydrogen storage and desorption performance.

[0042] In the present invention, the magnesium-rare earth alloy powder contains 1wt% to 6wt% of rare earth. For example, the content of rare earth in the magnesium-rare earth alloy powder can be 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt% or 6wt%, etc., or it can be other values ​​within the range of 1wt% to 6wt%.

[0043] If the rare earth content is too little, it will be unfavorable for the formation of γ'' phase, γ' phase and 14H-LPSO phase, and the rare earth element's own hydrogen storage and desorption capacity cannot be reflected, resulting in a certain degree of reduction in the amount of hydrogen desorption; if the rare earth content is too much, the rare earth element itself has a high viscosity, making it difficult to disperse evenly in the material, and the cost is high.

[0044] The particle size of the magnesium-rare earth alloy powder is 20 μm to 50 μm, such as 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm, etc., and may also be other values ​​within the range of 20 μm to 50 μm.

[0045] If the particle size of the magnesium-rare earth alloy powder is less than 20μm, the magnesium powder has high activity, the temperature is high during high-energy ball milling, and safety is difficult to ensure; if the particle size of the magnesium-rare earth alloy powder is greater than 50μm, it is not conducive to reacting with nickel powder to form γ'' phase, γ' phase and 14H-LPSO phase, which is not conducive to improving the hydrogen storage and desorption performance.

[0046] The multiphase coupled magnesium-based composite hydrogen storage material has 10vt%~15vt% long-period ordered stacking 14H-LPSO phase, 2vt%~5vt% single-layer γ" phase and 5vt%~10vt% single-layer γ' phase distributed inside the grains.

[0047] Among them, the γ'' phase and the γ' phase play an important role in improving the hydrogen storage performance. The γ'' phase has a single-layer structure and can absorb hydrogen at a lower temperature, while the γ' phase can release hydrogen at a lower temperature. The presence of these two phases enables the magnesium-based hydrogen storage material to effectively and quickly absorb and release hydrogen under different temperature conditions. By controlling the ratio and distribution of the γ'' phase and the γ' phase within the scope of the present invention, the hydrogen storage and desorption capacity and desorption temperature of the magnesium-based hydrogen storage material can be effectively optimized. The LPSO phase can promote the diffusion and adsorption of hydrogen atoms by providing a shorter hydrogen diffusion path and a lower energy barrier, thereby helping to improve the hydrogen storage rate and capacity of the material. The hydrogen storage capacity of the alloy containing a fine 14H-LPSO phase is more than 1.3 times that of the alloy with a coarse 18R-LPSO phase. The present invention is conducive to promoting the generation of a small-sized 14H-LPSO phase and avoiding the precipitation of a coarse 18R-LPSO phase by controlling the content and particle size of the nano-nickel powder. Through the coupling effect between the single-layer γ'' phase, the single-layer γ' phase and the 14H-LPSO phase, the grain size of the magnesium-based composite hydrogen storage material can be significantly refined, the hydrogen absorption and desorption capacity of the magnesium-based composite hydrogen storage material can be greatly increased, the initial desorption temperature can be reduced, and its hydrogen storage and desorption performance can be improved.

[0048] In some optional embodiments, the particle size of the multi-phase coupled magnesium-based composite hydrogen storage material may be 0.3 μm to 1 μm, such as 0.78 μm to 0.86 μm.

[0049] In some optional embodiments, the hydrogen absorption capacity of the multi-phase coupled magnesium-based composite hydrogen storage material is not less than 4.0 wt%, such as 4.0 wt% to 5.8 wt%.

[0050] In some optional embodiments, the initial dehydrogenation temperature of the multi-phase coupled magnesium-based composite hydrogen storage material is not higher than 300°C, such as 210°C to 262°C.

[0051] In some optional embodiments, the hydrogen release amount of the multi-phase coupled magnesium-based composite hydrogen storage material is not less than 3.0 wt%, such as 3.2 wt% to 5.2 wt%.

[0052] Correspondingly, the present invention also provides a method for preparing the above-mentioned multiphase coupled magnesium-based composite hydrogen storage material, comprising the following steps: ultrasonically dispersing the nano-nickel powder and drying it; then mixing it with the magnesium-rare earth alloy powder and vibrating and dispersing it; then performing multiple ball millings in an alternating manner of high-energy ball milling and low-energy ball milling under the protection of an inert gas, and then performing activation treatment.

[0053] In some optional embodiments, the frequency of ultrasonic dispersion can be 20KHz~25KHz, such as 20KHz, 21KHz, 22KHz, 23KHz, 24KHz or 25KHz, or other values ​​within the range of 20KHz~25KHz.

[0054] The ultrasonic dispersion time can be 20 min to 40 min, such as 20 min, 25 min, 30 min, 35 min or 40 min, etc., or other values ​​within the range of 20 min to 40 min.

[0055] By first ultrasonically dispersing the nano nickel powder and then mixing it with the magnesium-rare earth alloy powder, it is beneficial to improve the agglomeration of the nano nickel powder and facilitate the subsequent uniform distribution of the nickel powder on the surface of the magnesium-rare earth powder.

[0056] In some optional embodiments, the frequency of vibration dispersion may be 30 Hz to 40 Hz, such as 30 Hz, 32 Hz, 35 Hz, 38 Hz or 40 Hz, or other values ​​within the range of 30 Hz to 40 Hz.

[0057] The vibration dispersion time can be 30 minutes to 1 hour, such as 30 minutes, 40 minutes, 50 minutes or 1 hour, or other values ​​within the range of 30 minutes to 1 hour.

[0058] Vibration dispersion can alleviate the serious agglomeration of nano-nickel powder, which is helpful for the subsequent uniform distribution of nickel powder on the surface of magnesium powder, thereby promoting the formation of γ'' phase, γ' phase and 14H LPSO phase with nickel as active site.

[0059] In some optional embodiments, the rotation speed of the high energy ball mill can be 180rpm~250rpm, such as 180rpm, 190rpm, 200rpm, 210rpm, 220rpm, 230rpm, 240rpm or 250rpm, etc., or other values ​​within the range of 180rpm~250rpm.

[0060] The time of a single high-energy ball milling can be 30 min to 1 h, such as 30 min, 40 min, 50 min or 1 h, etc., or other values ​​within the range of 30 min to 1 h.

[0061] The ball-to-material ratio of high energy ball milling can be 20:1 to 30:1, such as 20:1, 25:1 or 30:1, or other values ​​within the range of 20:1 to 30:1.

[0062] In some optional embodiments, the rotation speed of the low energy ball mill can be 100 rpm to 150 rpm, such as 100 rpm, 110 rpm, 120 rpm, 130 rpm, 140 rpm or 150 rpm, etc., or other values ​​within the range of 100 rpm to 150 rpm.

[0063] The time of a single low-energy ball milling can be 30 min to 1 h, such as 30 min, 40 min, 50 min or 1 h, etc., or other values ​​within the range of 30 min to 1 h.

[0064] The ball-to-material ratio of low-energy ball milling can be 20:1 to 30:1, such as 20:1, 25:1 or 30:1, or other values ​​within the range of 20:1 to 30:1.

[0065] The high energy ball milling and the low energy ball milling may be performed alternately 5 to 10 times, such as 5 times, 6 times, 7 times, 8 times, 9 times or 10 times.

[0066] As mentioned above, by performing multiple ball millings in an alternating manner of first high-energy ball milling and then low-energy ball milling, the powder can produce an appropriate amount of plastic deformation and phase change, promoting the formation of a certain volume fraction of γ'' phase, γ' phase and 14H-LPSO phase. If high-energy ball milling is performed only at high speed, the powder is easily pressed into flakes by the grinding balls, and severe deformation leads to a decrease in the specific surface area of ​​the powder, which reduces the rate of hydrogen absorption and desorption reactions; at the same time, because the magnesium-rare earth powder has high viscosity, the deformed powder after high-energy ball milling adheres to the bottom of the ball mill, reducing the yield of the material. If low-energy ball milling is performed only at a low speed, the driving force is insufficient, and the conditions for the thermodynamic reaction between the nano-nickel powder and the magnesium-rare earth alloy powder are not fully met, which easily leads to the inability to simultaneously generate the γ'' phase, γ' phase and 14H-LPSO phase. If the ball milling is performed alternately in a manner of first low-energy ball milling and then high-energy ball milling, the nano-nickel powder is easily concentrated in the local area of ​​the magnesium-rare earth powder, which is not conducive to the uniformity of the material composition.

[0067] In some optional embodiments, the activation treatment may be performed at a temperature of 300° C. to 400° C. and a hydrogen pressure of 0.5 MPa to 3 MPa for 2 h to 3 h.

[0068] The temperature of the activation treatment may be 300°C, 320°C, 340°C, 360°C, 380°C or 400°C, or other values ​​within the range of 300°C to 400°C.

[0069] The activation process removes the oxide layer and impurities on the alloy surface and optimizes the alloy's microstructure, thereby significantly improving the hydrogen storage performance of the magnesium alloy. If the activation treatment temperature is lower than 300°C, the thermodynamic temperature of the oxide layer and hydrogen reaction is not reached, and the oxide layer still exists to hinder the subsequent hydrogen absorption and desorption reactions, and the activation effect cannot be achieved; if the activation treatment temperature is higher than 400°C, the high temperature magnesium-based composite hydrogen storage material is prone to excessive grain growth, which will reduce the subsequent hydrogen absorption and desorption reaction rate.

[0070] The pressure of the activation treatment may be 0.5 MPa, 1 MPa, 1.5 MPa, 2 MPa, 2.5 MPa or 3 MPa, etc., or may be other values ​​within the range of 0.5 MPa to 3 MPa.

[0071] If the activation treatment pressure is higher than 3MPa, the bond between the material and hydrogen will be more stable, which is more conducive to the hydrogen absorption reaction and not conducive to the increase of hydrogen release rate and amount.

[0072] The activation treatment time can be 2 h, 2.5 h or 3 h, etc., or other values ​​within the range of 2 h to 3 h.

[0073] The above activation treatment time can promote the formation of small-sized 14H-LPSO phase and avoid the precipitation of coarse 18R-LPSO phase. If the activation treatment time is less than 2 hours, it is easy to cause the surface oxide layer to fail to react completely with hydrogen, and the residual oxide layer on the surface hinders the internal material from absorbing and releasing hydrogen, causing the performance to drop significantly; if the activation treatment time is more than 3 hours, it is easy to cause all three phases to coarsen and grow into large-sized 18R-LPSO phase, which is not conducive to the absorption and release of hydrogen.

[0074] In addition, the present invention also provides an application of the above-mentioned multi-phase coupled magnesium-based composite hydrogen storage material, which can be used, for example, in a fuel cell hydrogen storage system.

[0075] Among them, the fuel cell hydrogen storage system can be exemplarily an automobile fuel cell hydrogen storage system or a military fuel cell hydrogen storage system, etc.

[0076] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0077] Example 1

[0078] This embodiment provides a multiphase coupled magnesium-based composite hydrogen storage material (MgNi5Y5 composite hydrogen storage material), and the preparation method thereof includes:

[0079] S1: ultrasonically dispersing the nano nickel powder and drying it.

[0080] The particle size of the nano nickel powder is 300 nm, the frequency of ultrasonic dispersion is 25 KHz, and the time of ultrasonic dispersion is 30 min.

[0081] S2: Mix the dried nano nickel powder in S1 with the magnesium-rare earth alloy powder, and disperse them by vibration.

[0082] The magnesium-rare earth alloy powder is a Mg5Y alloy powder containing 5wt% Y, the nano nickel powder accounts for 5wt% of the Mg5Y alloy powder, and the particle size of the Mg5Y alloy powder is 20μm. The frequency of the vibration dispersion is 35Hz, and the vibration dispersion time is 1h.

[0083] S3: The mixed powder dispersed by vibration in S2 is ball milled multiple times in an alternating manner of high-energy ball milling and low-energy ball milling under the protection of an inert gas.

[0084] Among them, the inert gas is argon; the rotation speed of the high-energy ball mill is 200 rpm, the time of a single high-energy ball milling is 30 min, and the ball-to-material ratio is 25:1; the rotation speed of the low-energy ball mill is 100 rpm, the time of a single low-energy ball milling is 30 min, and the ball-to-material ratio is 25:1; the number of alternating times of high-energy ball milling and low-energy ball milling is 8 times.

[0085] S4: activating the ball-milled material obtained by ball milling.

[0086] The activation treatment temperature is 350°C, the hydrogen pressure is 2MPa, and the activation time is 2.5h.

[0087] Example 2

[0088] This embodiment provides a multiphase coupled magnesium-based composite hydrogen storage material, and the preparation method thereof includes:

[0089] S1: ultrasonically dispersing the nano nickel powder and drying it.

[0090] The particle size of the nano nickel powder is 100 nm, the frequency of ultrasonic dispersion is 20 KHz, and the time of ultrasonic dispersion is 20 min.

[0091] S2: Mix the dried nano nickel powder in S1 with the magnesium-rare earth alloy powder, and disperse them by vibration.

[0092] The magnesium-rare earth alloy powder is a Mg1Y alloy powder containing 1wt% Y, the nano nickel powder accounts for 8wt% of the Mg1Y alloy powder, and the particle size of the Mg1Y alloy powder is 30μm. The frequency of the vibration dispersion is 30Hz, and the vibration dispersion time is 1h.

[0093] S3: The mixed powder dispersed by vibration in S2 is ball milled multiple times in an alternating manner of high-energy ball milling and low-energy ball milling under the protection of an inert gas.

[0094] Among them, the inert gas is helium; the rotation speed of the high-energy ball mill is 180rpm, the time of a single high-energy ball milling is 1h, and the ball-to-material ratio is 20:1; the rotation speed of the low-energy ball mill is 120rpm, the time of a single low-energy ball milling is 1h, and the ball-to-material ratio is 20:1; the number of alternating times of high-energy ball milling and low-energy ball milling is 5 times.

[0095] S4: activating the ball-milled material obtained by ball milling.

[0096] The activation treatment temperature is 300°C, the hydrogen pressure is 2.5MPa, and the activation time is 3h.

[0097] Example 3

[0098] This embodiment provides a multiphase coupled magnesium-based composite hydrogen storage material, and the preparation method thereof includes:

[0099] S1: ultrasonically dispersing the nano nickel powder and drying it.

[0100] The particle size of the nano nickel powder is 500 nm, the frequency of ultrasonic dispersion is 25 KHz, and the time of ultrasonic dispersion is 40 min.

[0101] S2: Mix the dried nano nickel powder in S1 with the magnesium-rare earth alloy powder, and disperse them by vibration.

[0102] The magnesium-rare earth alloy powder is a Mg6Y alloy powder containing 6wt% Y, the nano nickel powder accounts for 10wt% of the Mg6Y alloy powder, and the particle size of the Mg6Y alloy powder is 50μm. The frequency of the vibration dispersion is 40Hz, and the vibration dispersion time is 30min.

[0103] S3: The mixed powder dispersed by vibration in S2 is ball milled multiple times in an alternating manner of high-energy ball milling and low-energy ball milling under the protection of an inert gas.

[0104] Among them, the inert gas is a mixture of argon and helium; the rotation speed of the high-energy ball mill is 250rpm, the time of a single high-energy ball milling is 45min, and the ball-to-material ratio is 30:1; the rotation speed of the low-energy ball mill is 150rpm, the time of a single low-energy ball milling is 45min, and the ball-to-material ratio is 30:1; the number of alternating times of high-energy ball milling and low-energy ball milling is 10 times.

[0105] S4: activating the ball-milled material obtained by ball milling.

[0106] The activation treatment temperature is 400°C, the hydrogen pressure is 3MPa, and the activation time is 2h.

[0107] Example 4

[0108] The difference between this embodiment and embodiment 1 is that the rare earth element is lanthanum.

[0109] Example 5

[0110] The difference between this embodiment and embodiment 1 is that the rare earth element is cerium.

[0111] Example 6

[0112] The difference between this embodiment and embodiment 1 is that the rare earth element is praseodymium.

[0113] Example 7

[0114] The difference between this embodiment and embodiment 1 is that the rare earth element is neodymium.

[0115] Comparative Example 1

[0116] The difference between this comparative example and Example 1 is that the nano nickel powder accounts for 2wt% of the magnesium-rare earth alloy powder.

[0117] Comparative Example 2

[0118] The difference between this comparative example and Example 1 is that the nano nickel powder accounts for 15wt% of the magnesium-rare earth alloy powder.

[0119] Comparative Example 3

[0120] The difference between this comparative example and Example 1 is that the particle size of the nano nickel powder is 50 nm.

[0121] Comparative Example 4

[0122] The difference between this comparative example and Example 1 is that the particle size of the nano nickel powder is 600 nm.

[0123] Comparative Example 5

[0124] The difference between this comparative example and Example 1 is that the magnesium-rare earth alloy powder contains 0.5 wt % of rare earth.

[0125] Comparative Example 6

[0126] The difference between this comparative example and Example 1 is that the magnesium-rare earth alloy powder contains 8 wt % of rare earth.

[0127] Comparative Example 7

[0128] The difference between this comparative example and Example 1 is that the particle size of the magnesium-rare earth alloy powder is 100 μm.

[0129] Comparative Example 8

[0130] The difference between this comparative example and Example 1 is that the ultrasonic dispersion in S1 is not performed, and the nano nickel powder is directly dried and mixed with the magnesium-rare earth alloy powder in S2, and then dispersed by vibration. The remaining steps are the same as in Example 1.

[0131] Comparative Example 9

[0132] The difference between this comparative example and Example 1 is that high-energy ball milling is always performed in S3, and the total ball milling time remains unchanged.

[0133] Comparative Example 10

[0134] The difference between this comparative example and Example 1 is that low-energy ball milling is always performed in S3, and the total ball milling time remains unchanged.

[0135] Comparative Example 11

[0136] The difference between this comparative example and Example 1 is that in S3, low-energy ball milling is performed first and high-energy ball milling is performed alternately.

[0137] Comparative Example 12

[0138] The difference between this comparative example and Example 1 is that in S4, the activation treatment time is 1 h.

[0139] Comparative Example 13

[0140] The difference between this comparative example and Example 1 is that in S4, the activation treatment time is 4 hours.

[0141] Test example

[0142] ① Taking the multiphase coupled magnesium-based composite hydrogen storage material prepared in Example 1 as an example, the morphology thereof was tested, and the results are as follows: Figure 1 As shown, the morphology of the precipitated phase was detected, and the results were as follows Figure 2 The transmission fine structure characterization of the γ'' phase, γ' phase and 14H-LPSO phase in the multiphase coupled magnesium-based composite hydrogen storage material is shown in the figure. Figures 3 to 5 shown.

[0143] Depend on Figure 1 It can be seen that the precipitated phase of the multiphase coupled magnesium-based composite hydrogen storage material is very uniformly distributed, without obvious and serious segregation phenomenon.

[0144] Depend on Figure 2 It can be seen that: the γ'' phase, γ' phase and 14H-LPSO phase exist simultaneously inside the multiphase coupled magnesium-based composite hydrogen storage material;

[0145] Depend on Figure 3 It can be seen that the single-layer γ'' phase is distributed inside the grains of the multiphase coupled magnesium-based composite hydrogen storage material;

[0146] Depend on Figure 4 It can be seen that the single-layer γ' phase is distributed inside the grains of the multiphase coupled magnesium-based composite hydrogen storage material;

[0147] Depend on Figure 5It can be seen that the long-period ordered stacking 14H-LPSO phase is distributed inside the grains of the multiphase coupled magnesium-based composite hydrogen storage material.

[0148] From above, Figures 1 to 5 It can be seen that in the multiphase coupled magnesium-based composite hydrogen storage material obtained in Example 1, the three precipitated phases (γ'' phase, γ' phase and 14H-LPSO phase) are orderly arranged inside the multiphase coupled magnesium-based composite hydrogen storage material. In addition, the grain size of the magnesium-based composite material is relatively small, basically in the range of 0.3μm~1μm, which is conducive to the occurrence of hydrogen storage and desorption reactions.

[0149] ②. The multiphase coupled magnesium-based composite hydrogen storage materials prepared in Examples 1 to 7 and Comparative Examples 1 to 13 were tested for grain size, hydrogen absorption, hydrogen release and initial hydrogen release temperature. The results are shown in Tables 1 and Figure 6 to Figure 7 As shown. The hydrogen absorption and desorption curves are tested according to the pressure-composition-isotherm (PCT) test method for reversible hydrogen absorption and desorption of hydrides in GB / T 33291-2016.

[0150] Depend on Figure 6 It can be seen that the hydrogen absorption capacity of the multiphase coupled magnesium-based composite hydrogen storage material prepared in Example 1 is 5.8wt%.

[0151] Figure 7 It can be seen that the initial dehydrogenation temperature of the multiphase coupled magnesium-based composite hydrogen storage material prepared in Example 1 is reduced to 250° C., and the dehydrogenation amount is 5.2 wt %.

[0152] Table 1 Powder particle size and hydrogen absorption and desorption performance of magnesium-based composite hydrogen storage materials

[0153]

[0154] It can be seen from Table 1 that the multiphase coupled magnesium-based composite hydrogen storage material provided in the embodiment of the present invention has a smaller grain size, a higher hydrogen absorption capacity, a higher hydrogen desorption capacity and a lower initial hydrogen desorption temperature than the multiphase coupled magnesium-based composite hydrogen storage material provided in the comparative example.

[0155] In summary, the present invention provides a multiphase coupled magnesium-based composite hydrogen storage material, which is a nano-sized and alloyed composite material obtained by high-energy ball milling. The interior of the grains contains a single layer of γ'', a single layer of γ' phase and a small-sized 14H-LPSO phase. The hydrogen storage and desorption performance of the composite material is improved through the three-phase coupling effect.

[0156] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A multiphase coupled magnesium-based composite hydrogen storage material, characterized in that: The raw materials for preparing the multi-phase coupled magnesium-based composite hydrogen storage material include nano nickel powder and magnesium-rare earth alloy powder; The nano nickel powder accounts for 5wt% to 10wt% of the magnesium-rare earth alloy powder, and the particle size of the nano nickel powder is 100nm to 500nm; The magnesium-rare earth alloy powder contains 1wt% to 6wt% of rare earth, wherein the rare earth includes at least one of lanthanum, cerium, praseodymium, yttrium and neodymium; the particle size of the magnesium-rare earth alloy powder is 20μm to 50μm; The multiphase coupled magnesium-based composite hydrogen storage material has 10vt% to 15vt% of long-period ordered stacking 14H-LPSO phase, 2vt% to 5vt% of single-layer γ'' phase and 5vt% to 10vt% of single-layer γ' phase distributed inside the grains.

2. The multiphase coupled magnesium-based composite hydrogen storage material according to claim 1, characterized in that: The multiphase coupled magnesium-based composite hydrogen storage material also has at least one of the following characteristics: Feature 1: The grain size of the multiphase coupled magnesium-based composite hydrogen storage material is 0.3 μm to 1 μm; Feature 2: The hydrogen absorption capacity of the multiphase coupled magnesium-based composite hydrogen storage material is not less than 4.0wt%; Feature 3: The initial hydrogen release temperature of the multiphase coupled magnesium-based composite hydrogen storage material is not higher than 300°C; Feature 4: The hydrogen release capacity of the multiphase coupled magnesium-based composite hydrogen storage material is not less than 3.0wt%.

3. A method for preparing a multiphase coupled magnesium-based composite hydrogen storage material as claimed in claim 1 or 2, characterized in that: The following steps are involved: The nano nickel powder is ultrasonically dispersed and dried; then mixed with the magnesium-rare earth alloy powder and dispersed by vibration; then ball milled multiple times in an alternating manner of high energy ball milling and low energy ball milling under the protection of an inert gas, and then activated; The activation treatment is carried out at a temperature of 300°C to 400°C and a hydrogen pressure of 0.5MPa to 3MPa for 2h to 3h.

4. The preparation method according to claim 3, characterized in that: The frequency of ultrasonic dispersion is 20KHz~25KHz, and the time of ultrasonic dispersion is 20min~40min.

5. The preparation method according to claim 3, characterized in that: The frequency of vibration dispersion is 30Hz~40Hz, and the time of vibration dispersion is 30min~1h.

6. The preparation method according to claim 3, characterized in that: The rotation speed of high-energy ball milling is 180rpm~250rpm, the time of single high-energy ball milling is 30min~1h, and the ball-to-material ratio is 20:1 to 30:

1.

7. The preparation method according to claim 3, characterized in that: The rotation speed of low-energy ball milling is 100rpm~150rpm, the time of single low-energy ball milling is 30min~1h, and the ball-to-material ratio is 20:1 to 30:

1.

8. The preparation method according to claim 3, characterized in that: The alternating times of high energy ball milling and low energy ball milling is 5 to 10 times.

9. Use of the multiphase coupled magnesium-based composite hydrogen storage material as claimed in claim 1 or 2 in a fuel cell hydrogen storage system.

Citation Information

Patent Citations

  • Preparation method of Mg-RE-Ni alloy hydrogen storage material

    CN101962724A

  • Magnesium-based hydrogen storage alloy with long period structure and preparation method thereof

    CN102337438A

Cited By

  • Preparation of hydrogen storage material and hydrogen storage method

    CN121626932A